Eletrocoagulação seguida de filtração direta para tratamento de efluente de suinocultura - Crivilim, Bruna Raña (2021)
The existence of policies aimed at the sustainable development of countries has resulted in important changes in the process of conscious disposal of industrial effluents. In the scope of agro-industries, those that perform the slaughter of pigs are highlighted, since these wastes are rich in organic matter and microbial load that, when not treated, represent an economic and environmental problem due to their high toxicity, high pollution potential and constant threat to public health. Among the various methods of effluent treatments, the use of electrocoagulation (EC) is presented as an alternative because it is a diversified technique and the efficiency in the removal of various organic or inorganic pollutants. Thus, the objective was to verify if the electrocoagulation process with the use of aluminium and iron electrodes followed by direct filtration in sand can become an effective and efficient technology for the treatment of effluents from pig farming. The treatments involved performing EC followed by filtration. In the first stage, EC was performed under different pH conditions (acid, neutral and basic) and times (20.40 and 60 minutes) in addition to the analysis of two types of electrodes (aluminium and iron). The second stage was based on the direct filtration of the treated effluent, using sand filters with particle sizes between 0.4 and 0.85 mm. After the tests, the parameters: apparent color, turbidity, pH, Chemical Oxygen Demand (COD), total nitrogen, electrical conductivity, total solids (ST) and the metals aluminium, iron, copper, and zinc were analysed. The samples and their replicates were submitted to experimental planning, based on the variation of two variables (time and pH) in 3 levels, adding up to a total of 9 tests for each electrode and pH to be studied, totalling 54 tests. As for the results, it was obtained an overall efficiency for apparent color, turbidity, N-ammoniacal, COD, ST of 91%, 87%, 28%, 11% and 38%, respectively, for the effluent with neutral pH; 65%, 70%, 75%, 79% for basic pH and 99%, 99%, 67%, 86% and 33%, respectively, for acid pH. Statistically, for a significance level of p = 0.05, the change in pH was significant, but not over time, with acidic pH showing the best results. When the presence of metals was evaluated after the treatment of the effluent, it was possible to notice that, through the treatment by electrocoagulation with the use of both electrodes (aluminium and iron), no analysed metal was detected during the analysis. It is concluded that the proposed treatment proved to be partially effective, since even after the treatment with electrocoagulation and direct filtration as after treatment, remaining concentrations of ammoniacal nitrogen higher than acceptable in environmental legislation, as well as high concentrations, were still detected in the final effluent. of organic matter and total solids, thus showing the importance of post treatment and the need to include polishing treatment so that the effluent can be recommended for use.